Thai World Class Spa Business Development in Thailand towards Sustainability - กลั่นภักดี ภักดี; แสงพิกุล อัศวิน; คำสุพรหม ศิริเดช (Journal of Health Science of Thailand, 2020)
This paper focused on the development of Thai World Class Spa business reaching the Ministry of Public Health’s standard. It examined the demand of foreign tourists to understand the evolution of service quality, service marketing strategies, and customer satisfaction achievement which are the essential trends leading to the repurchase intention sustainability of foreign service receivers and the exact demand towards international tourists’ aspect. It also provided necessary information to be used for improving forms and service quality standards to meet the demand of target groups as closely as possible. Moreover, it noticed whether the existing structures or products linking to the market of foreign visitors, how they should be improved or developed, and problems of Thai World Class Spa businesses that can be addressed to support the development of the all-round quality of service standards. Also, the linkage between medical tourism and spa business can be identified, which can lead to the sustainable development of Thai world-class spa businesses.